Factors Affecting Diabetes Control And Dyslipidaemia Among Type 2 Diabetes Mellitus Patients In Hospital Universiti Sains Malaysia [RC660. E25 2003 f rb]. - Akhtar Mohammad, Eid Mohammad (2003)
This cross-sectional study was undertaken on 211 type 2 diabetic patients at the Outpatients Diabetes Clinic, HUSM Kubang Kerian, Kelantan between the year 2001 – 2002.